Non-traditional visualization in financial engineering for efficient portfolio management - Xiong, Fei. (2008)
As researchers begin to tackle larger and more complex problems, the need to collaborate within multi-disciplinary teams increases. Financial information visualization is a new research area that focuses on the use of visualization techniques to help people understand and analyze financial data. However, to build the visualization framework to tackle this cognition problem, we face two challenges. The first is Financial Complexity, which arises from the vast amount of data and complex financial models that handle it. The second is Visual Complexity, which arises from the lack of physical or geometric correspondence from data to spatial coordinates, and the poor choice of visual presentations.